Penerapan Pemberian Water Tepid Sponge Terhadap Penurunan Suhu Tubuh Pada Anak Toodler Dengan Hipertermi Di Ruang Anggrek RSUD Dr. Soeratno Gemolong - Issemi Lestari; Anjar Nurrohmah; Fitria Purnamawati (Lembaga Pengembangan Kinerja Dosen, 2023)
Background: Hyperthermia is a condition where the body temperature is higher than normal because the body is unable to dissipate excess heat in the body, which threatens to cause fever. The results of the medical records of the children's inpatient room at Dr Socratno Gemolong Hospital, the number of children treated at the Anggrek ward who experienced fever, namely preschool aged children in the last 4 months, was 116 patients. Efforts to reduce fever can use Water Tepid Sponge. Water Tepid Sponge is a warm compress action using wipes and blocks not only in one place. Objective: The aim is to find out the results of the implementation of giving Water Edged Sponge to body temperature due to fever. Methods: using a case study design, subjects were 2 pre-school aged children who were treated in the orchid children’s room at dr. Soeratno Gemolong hospital. The instrument used to measure body temperature is a thermometer. Application of water tepid sponge was carried out for 3 days. Findings: water tepid sponge is able to reduce body temperature in pre-school aged children (1-3 years) with hypertermia. Implication: there are dfferences in the develoment of decreased body temperature in pediatric patients with hypertermia before and after the application of the water tepid sponge. So that the action of water tepid sponges can be used as a non-pharmacological technique to reduce body temperature in pre-school aged children (1-3 years) with hyperthermia.